Natural Resources, Innovation, and Growth - Elissaios Papyrakis; Reyer Gerlagh (Fondazione Eni Enrico Mattei (FEEM), 2004)
This paper investigates the connection between resource abundance and innovation, as a transmission mechanism that can elucidate part of the resource curse hypothesis; i.e. the observed negative impact of resource wealth on income growth. We develop a variation of the Ramsey-Cass-Koopmans model with endogenous growth to explain the phenomenon. In this model, consumers trade off leisure versus consumption, and firms trade off innovation efforts versus manufacturing. For this model, we show that an increase in resource income frustrates economic growth in two ways: directly by reducing work effort and indirectly by inducing a smaller proportion of the labor force to engage in innovation.
Keywords: O13; O31; Q33; 330; Natural resources; Growth; Innovation; Natürliche Ressourcen; Wirtschaftswachstum; Innovation; Endogenes Wachstumsmodell